STRATEGI PENGEMBANGAN PARIWISATA DI SEPANJANG SUNGAI KAPUAS KOTA PONTIANAK - RISKA APRILIA AYUNINGTYAS; SRI HIDAYATI DJOEFFAN (Program Studi Perencanaan Wilayah dan Kota, UPT Publikasi Publikasi Ilmiah UNISBA, 2010)
Tourism is one sector development promoted by the government. Various efforts have been made such as Indonesia cooperation in economics, such as IMT-GT, IMS-GT, AFTA / AFAS, but still not very effective and satisfactory growth in the region in promoting such cooperation, because the disparity in growth. Perhaps that was one other limiting factor is the condition of the sub-region are varied so that the effect on accessibility. The uniformity of the tourism potential of Indonesia and other countries Indonesia makes tourism less popular, in addition to a lack of tourism promotion abroad. In addition, price competition and a lack of marketing of tourism in Indonesia has less in demand in the international market. The tourism sector is an important foreign exchange accounted for Indonesia.Until now Indonesia attraction yet fully explored. For example, in Pontianak itself, has a very good nature and attractive to tourists due to the attraction still original, exotic and diverse. However, these objects must be addressed properly to make it more beautiful and attractive place to visit ranging from complete facilities and infrastructure, and accessibility are still lacking support.Therefore, it is necessary to establish priorities and indications of tourism development programs in Pontianak that may be developed in the foreseeable datang.dengan using SWOT analysis. Analysis of the supply comes from ODTW analysis, requirements analysis of tourism facilities, tourism services needs analysis, estimation and analysis infrastructure and the environment. Analysis of supply and demand analysis is a matrix of strategic data to internal factors (IFAS) and external factors (EFAS) program as well as some recommendations for the development of Tourism for the City of Pontianak, the government participate in activities as their main duty to participate in the promotion of destinations, development of basic infrastructure in tourist objects are not managed by the private sector as a simple dock, toilets, mosque and construction of the entertainment / arts performances place.